2018
DOI: 10.1016/j.pscychresns.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Altered anterior cingulate cortex to hippocampus effective connectivity in response to drug cues in men with cocaine use disorder

Abstract: Drug-related attentional bias may have significant implications for the treatment of cocaine use disorder (CocUD). However, the neurobiology of attentional bias is not completely understood. This study employed dynamic causal modeling (DCM) to conduct an analysis of effective (directional) connectivity involved in drug-related attentional bias in treatment-seeking CocUD subjects. The DCM analysis was conducted based on functional magnetic resonance imaging (fMRI) data acquired from fifteen CocUD subjects while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 55 publications
7
24
0
Order By: Relevance
“…Similar process has been shown in other kinds of addiction, i.e. game, internet, and Prawiroharjo 16 pornography addiction [8,12,17,26,[34][35][36]. Decline in working memory affects goal-oriented behaviour greatly, as aforementioned maintained by PFC and corticolimbic network [8,16], thus suggested the problem existence in pornography addiction [37].…”
Section: Correlation Analysissupporting
confidence: 63%
See 3 more Smart Citations
“…Similar process has been shown in other kinds of addiction, i.e. game, internet, and Prawiroharjo 16 pornography addiction [8,12,17,26,[34][35][36]. Decline in working memory affects goal-oriented behaviour greatly, as aforementioned maintained by PFC and corticolimbic network [8,16], thus suggested the problem existence in pornography addiction [37].…”
Section: Correlation Analysissupporting
confidence: 63%
“…Although drug addiction studies are appreciably more dominating than other kinds of addiction, similar findings have also been shown on other addictions, i.e. game, internet, and pornography addiction [8,12,17,26,[34][35][36].…”
Section: Correlation Analysissupporting
confidence: 54%
See 2 more Smart Citations
“…Damage to the cortico-striatal nervous system largely contributed to maladaptive invasive thinking. Imaging studies have found that addiction-related cues increased the activation in the ACC, amygdala, ventral striatum, NAcc in addictive disorders, such as drug use 35 , gambling 36 , and overeating 37 . On the contrary, increased activation in ACC and insular during the suppression of thoughts were found in comparison with free-thought conditions 38 .…”
Section: Neuroimaging Findings On Impulsivity and Thought Suppressionmentioning
confidence: 99%